Impact of preconception micronutrient supplementation on anemia and iron status during pregnancy and postpartum: A randomized controlled trial in rural Vietnam - Nguyen, Phuong Hong; Young, Melissa; Gonzalez-Casanova, Ines; Pham, Hoa Q.; Nguyen, Hieu; Nguyen, Son V.; Harding, Kimberly B.; Reinhart, Gregory A.; Martorell, Reynaldo; Ramakrishnan, Usha (Public Library of Science, 2016)
Objective Preconception micronutrient interventions may be a promising approach to reduce anemia and iron deficiency during pregnancy, but currently we have limited data to inform policies. We evaluated whether providing additional pre-pregnancy weekly iron-folic acid (IFA) or multiple micronutrient (MM) supplements compared to only folic acid (FA) improves iron status and anemia during pregnancy and early postpartum. Methods We conducted a double blind randomized controlled trial in which 5011 Vietnamese women were provided with weekly supplements containing either only 2800 μg FA (control group), IFA (60 mg Fe and 2800 μg FA) or MM (15 micronutrients with similar amounts of IFA). All women who became pregnant (n = 1813) in each of the 3 groups received daily IFA (60 mg Fe and 400 μg FA) through delivery. Hematological indicators were assessed at baseline (pre-pregnancy), during pregnancy, 3 months post-partum, and in cord blood. Adjusted generalized linear models were applied to examine the impact of preconception supplementation on anemia and iron stores, using both intention to treat and per protocol analyses (women consumed supplements ≥ 26 weeks before conception). Results At baseline, 20% of women were anemic, but only 14% had low iron stores (ferritin <30 μg/L) and 3% had iron deficiency (ferritin <12 μg/L). The groups were balanced for baseline characteristics. Anemia prevalence increased during pregnancy and post-partum but was similar among intervention groups. In intention to treat analyses, prenatal ferritin was significantly higher among women receiving MM (geometric mean (μg/L) [95% CI]: 93.6 [89.3–98.2]) and IFA (91.9 [87.6–96.3]) compared to control (85.3 [81.5–89.2]). In per protocol analyses, women receiving MM or IFA had higher ferritin 3 months postpartum (MM 118.2 [109.3–127.8]), IFA 117.8 [108.7–127.7] vs control 101.5 [94.0–109.7]) and gave birth to infants with greater iron stores (MM 184.3 [176.1–192.9]), IFA 189.9 [181.6–198.3] vs control 175.1 [167.9–182.6]). Conclusion Preconception supplementation with MM or IFA resulted in modest increases in maternal and infant iron stores but did not impact anemia. Further research is needed to characterize the etiology of anemia in this population and identify effective interventions for reducing prenatal anemia. Trial Registration ClinicalTrials.Gov NCT01665378